People participating in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. They are passing a Chevron gas station which is on the corner of the East Santa Clara Street and Fourth Street in downtown San Jose. The street sign behind them reads: "Fourt[h]."